Muhammad Iqbal and Division of Sub-continent - ., AllahDino; Soomro, Siraj Ahmed; Chandio, Jalil Ahmed (Journal of History Culture and Art Research, 2018)
Muhammad Iqbal was not a professional politician but at certain stages of his life he showed a keen interest in the politics of the sub-continent. Even in the area, he handled many complex problems with remarkable insight and left a permanent mark on the events which molded the destiny of the million. His participation in the political issues of the day was based on sincerely and conviction. He cherished peace and orders more than anything else in life. In order to understand the various aspects of Iqbal’s political career, it is essential to make a brief review of the contemporary political scene, when Iqbal turned his attention towards the political and constitutional problems which were ultimately to shape the future of the Indo-Pakistan subcontinent.